Cholestasis and hypercalcemia secondary to panhypopituitarism in a newborn - Dursun, Fatma; Gerenli, Nelgin; Kırmızıbekmez, Heves (The Turkish Journal of Pediatrics, 2017)
Cholestatic hepatitis and hypercalcemia are rare features of hypopituitarism in newborns. So diagnosis of hypopituitarism is frequently delayed. The most frequent symptoms of congenital hypopituitarism are hypoglycemia, prolonged jaundince and micropenis. A patient with congenital hypopituitarism associated with cholestasis and hypercalcemia is reported here. Newborns with hypercalcemia and cholestasis should alert pediatricians to the possibility of congenital hypopituitarism and prompt endocrinological investigation.